Extra bold : a feminist, inclusive, anti-racist, non-binary field guide for graphic designers - Lupton, Ellen (New York : Princeton Architectural Press, 2021)
"Critical essays link theories about feminism, racism, inclusion, and binary thinking to design principles and practices. Type specimens, biographies, and interviews showcase the work and ideas of people marginalized by sexism, racism, and/or ableism"--
Theory. Feminism -- Anti-stairs club -- Sex and gender terms -- History. Life : Yolande Bonhomme -- Feminism in India -- Timeline : queer history -- Work. Wage gaps -- Hiring for diversity -- Psychological safety.
Includes index.
Keywords: Design -- Human factors; Design -- Social aspects; Design -- Practice; Electronic books